2014
DOI: 10.1111/all.12426
|View full text |Cite
|
Sign up to set email alerts
|

Fatal anaphylaxis with neuromuscular blocking agents: a risk factor and management analysis

Abstract: Obese males with a history of cardiovascular disease receiving ongoing beta-blocker treatment and undergoing surgery in an emergency setting were at high risk of a fatal outcome after NMBA-induced anaphylaxis. Some epinephrine-resistant cases may play a role in our high mortality rate. New therapeutic approaches need to be developed to treat these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 24 publications
3
89
0
4
Order By: Relevance
“…Perioperative anaphylaxis in humans is uncommon, with an estimated incidence of 1 in 10,000 to 20,000 anaesthetics, but carries a mortality rate of around 4-10% (Axon and Hunter 2004, Dewachter et al 2009, Gibbs et al 2013, Harper et al 2009, Reitter et al 2014. From the limited number of published veterinary reports it is impossible to ascertain a mortality rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perioperative anaphylaxis in humans is uncommon, with an estimated incidence of 1 in 10,000 to 20,000 anaesthetics, but carries a mortality rate of around 4-10% (Axon and Hunter 2004, Dewachter et al 2009, Gibbs et al 2013, Harper et al 2009, Reitter et al 2014. From the limited number of published veterinary reports it is impossible to ascertain a mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is associated with a high mortality rate of approximately 4-10% (Axon and Hunter 2004, Gibbs et al 2013, Reitter et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…arterial hypotension, tachycardia) can have many other causes during anesthesia and surgery; anesthesia per se alters the compensatory mechanisms that an awake individual would mobilize during an anaphylactic reaction. This could explain the much higher fatality rate of AS during anesthesia (4.1%) [3], as compared to that of patients admitted to emergency departments for anaphylaxis (approximately 0.7/ million population) [4]. The specificities of anaphylaxis/AS during anesthesia and surgery, the object of this article, are related to the fact that within minutes, the anesthesiologist must recognize signs of anaphylaxis that can also much more frequently occur because of other causes (e.g.…”
Section: Definitionmentioning
confidence: 99%
“…A competitive tendering process for the right to run the CEMD was held in 2010, resulting in the award of the contract to a new consortium: Mothers and Babies -Reducing Risk through Audits and Confidential Enquiries across the UK (MBR-RACE-UK). Before it could start, but after the programmed demise of the Centre for Maternal and Child Enquiries (CMACE, which had been running the Enquiries previously) in 2011, a review panel was instructed to examine the requirements for the programme [4]. The review panel concluded that the maternal and infant enquiries should continue, and MBR-RACE-UK was reconfirmed in its status with a start date of May 2012 [1].…”
Section: Competing Interestsmentioning
confidence: 99%
“…Mortality from anaesthesia-related anaphylaxis is reported to be between 1.4% and 9% [3][4][5], and in the case of reactions to neuromuscular blocking drugs has been associated with male sex and a history of cardiovascular disease, including hypertension and ongoing beta-blocker treatment. The persisting relatively high mortality despite following international guidelines is suggested as reflecting the severity of reactions to these agents [4].…”
mentioning
confidence: 99%